Wiley 2019 interpretation and application of IFRS standards - Alibhai, Salim (John Wiley and Sons, Inc. : Wiley, 2019)
The 2019 reference for the interpretation and application of the latest international standards Wiley IFRS Standards 2019 is a revised and comprehensive resource that includes the information needed to interpret and apply the most recent International Financial Reporting Standards (IFRS) as outlined by the International Accounting Standards Board (IASB). This accessible resource contains a wide range of practical examples as well as invaluable guidance on the expanding framework for unified financial reporting. The authors provide IFRIC interpretations and directions designed to ensure a clear understanding of the most recent standards. The IFRS standards are ever evolving, therefore it is essential that professionals and students have the information needed to apply the standards correctly in real-world cases. Wiley IFRS Standards 2019 offers a complete, up-to-date reference that aids in the application of the latest international standards in a manner that is transparent, accountable and efficient. This edition includes IFRS 9 Financial Instruments; IFRS 15 Revenue from Contracts with Customers; IFRS 16 Leases and amendments issued and effective for annual periods beginning on or after 01 January 2018 and 01 January 2019 as issued by the IASB by 30 June 2018. This edition also includes some introductory guidance for IFRS 17 Insurance Contracts and incorporates the revised Conceptual Framework for Financial Reporting 2018. This important guide is written by the people passionate about IFRS at PKF International. PKF International consists of over 400 offices, operating in 150 countries across five regions. PKF International specialises in providing high quality audit, accounting, tax, and business advisory solutions to international and domestic organisations around the globe. PKF International is a global family of legally independent firms bound together by a shared commitment to quality, integrity and the creation of clarity in a complex regulatory environment. PKF International is a member of the Forum of Firms - an organisation dedicated to consistent and high-quality standards of financial reporting and auditing practices worldwide. www.pkf.com. PKF International Limited administers a family of legally independent firms and does not accept any responsibility or liability for the actions or inactions of any individual member or correspondent firm or firms. All rights reserved.